2011
DOI: 10.1177/107769581106600303
|View full text |Cite
|
Sign up to set email alerts
|

The Gap between Online Journalism Education and Practice: The Twin Surveys

Abstract: This U.S. national survey of online journalism professionals and instructors examines and compares their perceptions of skills, concepts, and duties. It offers updated insights into the changes taking place in online journalism classrooms and newsrooms, and uncovers the discordance between online journalism education and practice. The results show that online journalism education is tied to traditional journalism in many ways, but is not merely a more technologically focused version of traditional journalism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 0 publications
0
34
0
5
Order By: Relevance
“…como mediante aquellas que dan cuenta del ecosistema periodístico actual (digital, multimedia, etc. ), tal y como han establecido estudios anteriores (Huang et al, 2006;Pierce & Miller, 2007;Fahmy, 2008;Du & Thornburg, 2011;Arroyo Cabello, 2011;García-Santamaría & Barranquero Carretero, 2014;Poynter Institute, 2013). Pese a esto, las pruebas de evaluación que suministran los medios a los candidatos que aspiran reclutar otorgan mayor importancia a las destrezas tradicionales de redacción, sentido noticioso y al conocimiento en cultura general que a las multimedia y digitales.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…como mediante aquellas que dan cuenta del ecosistema periodístico actual (digital, multimedia, etc. ), tal y como han establecido estudios anteriores (Huang et al, 2006;Pierce & Miller, 2007;Fahmy, 2008;Du & Thornburg, 2011;Arroyo Cabello, 2011;García-Santamaría & Barranquero Carretero, 2014;Poynter Institute, 2013). Pese a esto, las pruebas de evaluación que suministran los medios a los candidatos que aspiran reclutar otorgan mayor importancia a las destrezas tradicionales de redacción, sentido noticioso y al conocimiento en cultura general que a las multimedia y digitales.…”
Section: Discussionunclassified
“…Se cuestiona la capacidad del profesorado y la calidad del currículo académico, porque se dice que no provee las destrezas necesarias para practicar adecuadamente el periodismo, ya sea porque enfatiza demasiado en la teoría, o porque simplemente solo enseña destrezas profesionales, dejando de lado la cultura y el conocimiento general. También, si se debe estudiar periodismo o si lo adecuado es que el futuro periodista reciba una educación más redondeada en diversas disciplinas, como economía y política, lo que ha llevado a disputar, además, dónde se localiza disciplinariamente el estudio del periodismo (School of Journalism, 1987;Weaver & Wilhoit, 1988;Fuentes Navarro, 1992;Reese, 1999;Dickson & Brandon, 2000ª, 2000bDeuze, 2004Deuze, , 2006Dates, 2006;Pierce & Miller, 2007;Nolan, 2008;King, 2008;Hirst, 2010;Du & Thornburg, 2011;Mellado, 2011). Ya de más reciente cuño se ha debatido qué tipo de destrezas un periodista debe manejar en un ecosistema digital y multimedia, y cómo se distancian de las que recibe en la academia, críticas que la califican como retrasada y como un ente marginal al campo (Carnegie-Knight Initiative on the Future of Journalism, 2011).…”
Section: El Campo Educativo Periodísticounclassified
See 1 more Smart Citation
“…There is also evidence that journalism students should learn mass communication theoretical knowledge if they want to evolve with the industry (Carpenter, 2009). Du and Thornburg (2011) reported that despite an agreement between online journalists and online journalism instructors about the importance of core skills (e.g., writing and grammar), there seems to be discord over the relative value of other competencies (e.g., multitasking, mass communication theory, interpersonal skills, etc.). As a response to rapid technological changes, some scholars (e.g., Doherty, 2012) have even argued that journalists need to learn computer science skills to regain control over their work.…”
Section: Balancing Journalistic Skills and Specialized Knowledgementioning
confidence: 99%
“…Fundamentally, this reflects the fact that there is a widely assumed gap between journalism education and practice -an issue that has been thoroughly researched and debated by scholars and practitioners in the last decades (Lepre and Bleske 2005;Dickson and Brandon 2000). These studies show a discrepancy between professionals and educators when it comes to understanding the importance of the skills needed for practice, but the gap is not particularly wide compared to other professions (Du and Thornburg 2011). The 'academization' of journalism has according to Splichal and Sparks (1994) sparked an interest for investigating how it prepares journalism students at university for a journalism career (Frith and Meech 2007;Franklin and Mensing 2014;Mellado et al 2012) and how their professional views are shaped (Hanitzsch et al 2011;Weaver and Willnat 2012;Hanusch and Mellado 2014).…”
Section: Introductionmentioning
confidence: 99%